Assessment essentials planning, implementing, and improving assessment in higher education - Banta, Trudy W.; Palomba, Catherine A. 1943- (San Francisco Jossey-Bass, 2015)
In this thoroughly revised edition of Assessment Essentials, the bestselling text on outcomes assessment in higher education, you will find, in a familiar framework, nearly all new material, examples from more than 100 campuses, and indispensable descriptions of direct and indirect assessment methods that have helped to educate faculty, staff, and students about assessment. Leading authorities Trudy Banta and Catherine Palomba draw on research, standards, and best practices to address the timeliest issues in higher education accountability. This edition includes information on the use of electronic portfolios, rubrics and course-embedded assessment, assessment in student affairs, and how to assess institutional effectiveness. -- from back cover.
1. Defining assessment -- 2. Assessment essentials -- 3. Engaging faculty and students in assessment -- 4. Setting expectations and preparing to select measures -- 5. Using direct measures -- 6. Using indirect assessment methods -- 7. Assessing learning in the major -- 8. Assessing learning in general education -- 9. Assessing student learning and program effectiveness in student affairs -- 10. Analyzing, reporting, and using assessment results -- 11. Assessing institutional effectiveness -- 12. Summing up: a time of transition.
Catherine A. Palomba is the first author on the title page of the first edition.
Includes bibliographical references and index.
Keywords: Universities and colleges -- United States -- Examinations